An ‘Old Amharic’ Commentary on the Nicene Creed - Appleyard, David L. (Aethiopica, 2003)
Translation of a pre-modern Amharic commentary on the Nicene Creed in English. The text of a Commentary on the Nicene Creed (ṣälotä haymanot) which forms the subject of this paper appears at the end of a copy of the Psalter and Wǝddase Maryam belonging to the Ethiopian church at Däbrä Gännät in Jerusalem [MS JE 48 E = MS Dabra Gannat 186]. The text was copied and circulated privately by the late Roger Cowley, who also records that material similar in outline but different in detail is contained in the andǝmta-commentary on the Anaphora of the Nicene Fathers.